1978
DOI: 10.1136/ard.37.3.212
|View full text |Cite
|
Sign up to set email alerts
|

Combination of theophylline and prostaglandin E1 as inhibitors of the adjuvant-induced arthritis syndrome of rats.

Abstract: SUMMARY The effects of daily subcutaneous administration of prostaglandin E1 (PGE,), theophylline, and of both drugs together were studied on the Freund's adjuvant-induced inflammatory and arthritic syndrome in rats. In the doses used, neither drug affected the acute inflammatory response in the adjuvant-treated paw, but together they caused marked inhibition. Chronic inflammation in the contralateral (nontreated) hind paws was slightly inhibited by each drug and combined treatment resulted in marked inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

1978
1978
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 18 publications
0
8
1
Order By: Relevance
“…This is in contrast to previous results (Aspinall and Cammarata, 1969;Zurier and Quagliata, 1971;Bonta et al, 1977bBonta et al, , 1978. However, there is some indication that low doses of PGE1 increase lysosomal enzyme release from granulocytes in vitro (Weissmann, 1972) and this may have accounted for the increase in paw volume in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previous results (Aspinall and Cammarata, 1969;Zurier and Quagliata, 1971;Bonta et al, 1977bBonta et al, , 1978. However, there is some indication that low doses of PGE1 increase lysosomal enzyme release from granulocytes in vitro (Weissmann, 1972) and this may have accounted for the increase in paw volume in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The inhibitory effects of PGE on leucocyte function in vitro are related to increases in intracellular cyclic AMP Accepted for publication September 5, 1977 Correspondence to Dr M. J. Parnham (cAMP) (Boume et al, 1974), and theophylline, an inhibitor of cAMP phosphodiesterase, was found in vivo to potentiate the PGE l-induced suppression of the arthritic syndrome (Bonta et al, 1977b(Bonta et al, , 1978.…”
mentioning
confidence: 99%
“…Inhibition of leukocyte infiltration in acute immune complex vasculitis after systemic administration of PGE1 and PGE: has been reported [3,11,17]. These prostaglandins participate in the activation of T-suppressor cells, thereby directly inhibiting the humoral response to a delayed hypersensitivity reaction [7].…”
Section: Discussionmentioning
confidence: 99%
“…PGE1 was used because it has been shown, by several authors, to be slightly more potent than PGE2 both in stimulating intracellular cyclic adenosine 3',5'-monophosphate (cyclic AMP) and in producing anti-inflammatory effects in vitro (Parker, 1972;Lichtenstein, 1974;Smith, 1977). Furthermore, while PGE2 is the more important endogenous prostaglandin of the E series released during inflammation in the rat (Youlten & McCall, 1976), the pharmacology of PGE, as an anti-inflammatory agent in vivo has been more extensively studied (Zurier & Quagliata, 1971;Zurier & Ballas, 1973;Zurier, Hoffstein & Weissmann, 1973;Nusbickel, 1976;Bonta, Parnham & van Vliet, 1978). Since experimental granulomata become more sensitive to the vascular permeability increasing effects of exogenous PGE1 and PGE2 as the inflammatory process becomes increasingly chronic , we treated the granulomata with PGE1 at different times to investigate possible changes in the effects of PGE, on developing granulomata.…”
Section: Introductionmentioning
confidence: 99%